2004
DOI: 10.1242/jeb.01052
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine stimulates snail albumen gland glycoprotein secretion through the activation of a D1-like receptor

Abstract: The catecholamine dopamine is present in both the central nervous system and in the peripheral tissues of molluscs, where it is involved in regulating reproduction. Application of exogenous dopamine to the isolated albumen gland of the freshwater pulmonate snail Helisoma duryi (Wetherby) induces the secretion (release) of perivitelline fluid. The major protein component of the perivitelline fluid of Helisoma duryi is a native 288·kDa glycoprotein that is secreted around individual eggs and serves as an importa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 49 publications
1
15
0
1
Order By: Relevance
“…In contrast, the dopamine D2 antagonist domperidone was ineffective (Fig.8B), consistent with other studies on gastropods in which responses were typically blocked by only one of these antagonist types (Mukai et al, 2004;Dobson et al, 2006). The ability of SKF83566 to lower the rate of rotation indicates that the cilia driving embryonic rotation receive tonic dopaminergic stimulation.…”
Section: Pharmacological Analysis Of the Hypoxia Responsesupporting
confidence: 88%
“…In contrast, the dopamine D2 antagonist domperidone was ineffective (Fig.8B), consistent with other studies on gastropods in which responses were typically blocked by only one of these antagonist types (Mukai et al, 2004;Dobson et al, 2006). The ability of SKF83566 to lower the rate of rotation indicates that the cilia driving embryonic rotation receive tonic dopaminergic stimulation.…”
Section: Pharmacological Analysis Of the Hypoxia Responsesupporting
confidence: 88%
“…To rule out a potential role of D1-like receptors in mediating the effect of DA on RMP, we used a D1 receptor antagonist, SCH23390, to investigate whether the DAinduced hyperpolarization could be blocked when the D1-like receptor was inhibited (Magoski et al, 1995;Mukai et al, 2004). Whereas the pretreatment with 100 lM SCH23390, a concentration that has been demonstrated to be effective in Lymnaea, did not affect the RMP of B5 neurons (+0.4 ± 1.3 mV; n = 4, Fig.…”
Section: A D2-like Receptor Mediates Da's Effect On Electrical Activitymentioning
confidence: 99%
“…It also produces significant amounts of Lymnaea trypsin inhibitor (LTI), which may minimize digestion of peptides (e.g., L-EGF) and proteins in the perivitelline fluid that are important for the development of the embryos (Nagle et al 2001). Secretion of glycoproteins of the perivitelline fluid is mediated by dopamine, and recent studies strongly suggested the presence of a dopamine D1-like receptor in the albumen gland of H. duryi (Mukai et al 2004). Other molecules, such as FMRFamide, are secreted by CNS cells and affect egg laying among many other functions including heart rhythm and respiration (Saunders et al 1992).…”
Section: Endogenous Factors External Stimulimentioning
confidence: 99%